Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.908077
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Effects and Mechanism of Curcumin in the Treatment of Inflammatory Bowel Disease

Abstract: Curcumin is extracted from the rhizomes of Curcuma longa L. It is now widely used in food processing, cosmetics, dyes, etc. Current researching indicates that curcumin has high medical value, including anti-inflammatory, antioxidant, anti-tumor, anti-apoptotic, anti-fibrosis, immune regulation and other effects, and can be used to treat a variety of diseases. Inflammatory bowel disease (IBD) is a nonspecific inflammatory disease of the intestine including Crohn’s disease (CD) and ulcerative colitis (UC). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Intestinal epithelial cells detect bacteria and other microorganisms through TLR4 and other pattern recognition receptors (PRR) expressed on immune cells, such as macrophages and DC cells [99]. These receptors identify pathogen-associated molecular patterns (PAMPs) on microorganisms, resulting in a normalized immune response [19].…”
Section: Immune Systemmentioning
confidence: 99%
“…Intestinal epithelial cells detect bacteria and other microorganisms through TLR4 and other pattern recognition receptors (PRR) expressed on immune cells, such as macrophages and DC cells [99]. These receptors identify pathogen-associated molecular patterns (PAMPs) on microorganisms, resulting in a normalized immune response [19].…”
Section: Immune Systemmentioning
confidence: 99%
“…Antioxidant balance is also regulated by curcumin in rats with UC by lowering both colonic MPO activity and total NO content as well as increasing colonic GST activity and GSH contents when administered prior to the DSS challenge ( 154 ). Curcumin has been shown to decrease OS markers MPO and MDA levels and cell apoptosis in different animal models of colitis ( 155 158 ) ( Supplementary Table 1 ).…”
Section: Role Of Antioxidants For Ibd-related Therapeutic Application...mentioning
confidence: 99%
“…Despite its unfavorable pharmacokinetic characteristics, growing evidence has shown that CUR has numerous pharmacological properties, including antimicrobial [ 76 ], antiviral [ 77 ], antifungal [ 78 ], antioxidant [ 79 ], anti-inflammatory [ 80 ], and also anti-tumoral properties [ 81 ]. In particular, CUR represents a promising phytochemical in the anti-cancer field to be used alone or combined with other drugs through different pathways ( Figure 2 ).…”
Section: Plant-derived Bioactive Compoundsmentioning
confidence: 99%